Dupla listagem e governança corporativa uma análise da valorização das ações das empresas brasileiras emissoras de ADRs em mercados de alta governança - Husek, Flávia Caprara (2012)
Corporate Governance has been the subject of a broad complex of articles within last decade, mainly related to the study regarding the appraisal of shares of publicly-held companies after the creation and implementation of all internal and external control mechanisms to comply with the requirements of Corporate Governance. The issue has became especially important after 2000, when the São Paulo Stock Exchange BOVESPA created the listing segments Level I, Level II and New Marked. Nevertheless, the association and connection of the subject Corporate Governance with the cross-listing matter is still very incipient, requiring deeper studies. This research has had as main purpose to broaden the discussions as regards the impact of issuance of shares in stock exchanges of countries with high Corporate Governance levels, in the shares traded by such companies in the São Paulo Stock Exchange, within the period from 2000 to 2011. Assuming the relation of cross-listing with the appraisal of Brazilian companies, an event study has been performed with the scope of verifying the existence of statistically material abnormal returns on the Brazilian shares at the date of issuance of American Depositary Receipts (ADRs). Utilyzing a sampling of 16 events of companies issuing shares in the New York Stock Exchange (NYSE), it has been verified that there is no statistically material positive valuation of the Brazilian shares at the time of ADRs issuance. The results verified ractify, in part, the null hypothesis that the issuance in more criterious markets do not direclty reflect in the Brazilian market, signaling that the internationalization, still considered costfull, is not yet positively evaluated by the marked